PENGARUH TEKNOLOGI TERHADAP PENDIDIKAN DI INDONESIA: SYSTEMATIC LITERATURE REVIEW - Sarwedi Harahap; Zulhamdani Napitupulu (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2023)
Education in Indonesia has undergone significant changes with the integration of technology. This research aims to systematically review the existing literature on the impact of technology on education in Indonesia. Using the Systematic Literature Review (SLR) method, we identify and analyze relevant studies to evaluate how technology has affected the quality of education, the learning process, and access to education in Indonesia. The analysis results show that technology has positively impacted the quality of learning through the use of digital tools and e-learning platforms. However, this research also reveals the challenges faced, including the technological access gap between urban and rural areas and the limitations of technological infrastructure. Additionally, the importance of teacher training in the use of technology is also highlighted. These findings provide insights for policymakers and education practitioners to formulate effective strategies in utilizing technology to enhance the quality of education in Indonesia.